Critical Success Factors and Processed Fruit Export Supply Chain Improvement of Thai SME to India - Janapiraganit, Tanaporn; Jongsureeyapart, Chatrudee (International Journal of Supply Chain Management, 2019)
This paper aims to explore business key success factors and readiness of Thai small to medium-sized enterprises (SMEs) manufacturing processed fruits to enhance processed fruit export supply chain from Thailand to India market. Business success factors were measured based on three dimensions; organization, technology, and environment. Then the correlation of factors were tested with an attentiveness to India market by using Paired-Sample t-test approach. Questionnaires were gathered totally from 111 processed-fruit SMEs in Thailand, especially tamarind, longan, and coconut enterprises. The findings reveal that governmental support, CEO’s experience, and quality of product are considered as critical success factors. However, to improve an export supply chain of processed fruit, the suggestions in context of 3Ps (Private, Public, and Partnership) has been applied.